Implementing a green bicycle alliance using a wireless sensor network. (20th August 2014) - Shin, Haw–Yun; Own, Chung–Ming
This study used the wireless sensor network (WSN) technique to design a bike device module, a bike path establishment module and a cloud service module. These three modules were used to address issues related to cycling activities, including green power supply, activity and health records, trajectory monitoring and group positioning and immediate safety issues. GPS was not required, and as long as the cyclists remained on the paths provided by the bike path establishment module and used the cloud service module, the previously mentioned issues could be addressed. The cloud service module included a path establishment simulation system that could enable a path manager to simulate paths before they were physically provided, to determine the ideal establishment method for providing wireless sensor nodes. This study use the Danshui Golden Waterfront in northern Taiwan to implement on–site establishment and installation.